2015
DOI: 10.1089/ten.tec.2014.0643
|View full text |Cite
|
Sign up to set email alerts
|

Dual Delivery of EPO and BMP2 from a Novel Modular Poly-ɛ-Caprolactone Construct to Increase the Bone Formation in Prefabricated Bone Flaps

Abstract: Poly-e-caprolactone (PCL) is a biocompatible polymer that has mechanical properties suitable for bone tissue engineering; however, it must be integrated with biologics to stimulate bone formation. Bone morphogenetic protein-2 (BMP2) delivered from PCL produces bone when implanted subcutaneously, and erythropoietin (EPO) works synergistically with BMP2. In this study, EPO and BMP2 are adsorbed separately on two 3D-printed PCL scaffold modules that are assembled for codelivery on a single scaffold structure. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Early work by Wagoner Johnson et al, demonstrated the use of 3D-printed hydroxyapatite ceramic scaffolds able to enhance bone ingrowth and healing in vivo (Woodard et al, 2007). Ongoing efforts by Hollister et al have demonstrated the use of polycaprolactone (PCL) constructs as well as additional control over incorporation of bioactive agents to enhancing biomolecule absorption and release (Patel et al, 2015a;Suarez-Gonzalez et al, 2012), gene transfer (Hu et al, 2009), and resultant in vivo treatment of both cartilage and bone defects (Jeong et al, 2011;Patel et al, 2015b). The nature of the PCL construct allows rapid patient customization.…”
Section: Introductionmentioning
confidence: 99%
“…Early work by Wagoner Johnson et al, demonstrated the use of 3D-printed hydroxyapatite ceramic scaffolds able to enhance bone ingrowth and healing in vivo (Woodard et al, 2007). Ongoing efforts by Hollister et al have demonstrated the use of polycaprolactone (PCL) constructs as well as additional control over incorporation of bioactive agents to enhancing biomolecule absorption and release (Patel et al, 2015a;Suarez-Gonzalez et al, 2012), gene transfer (Hu et al, 2009), and resultant in vivo treatment of both cartilage and bone defects (Jeong et al, 2011;Patel et al, 2015b). The nature of the PCL construct allows rapid patient customization.…”
Section: Introductionmentioning
confidence: 99%
“…CVD Polymerization : PCL, PLGA, and titanium discs were coated with a layer of amine‐reactive polymer using a custom‐built CVD system previously reported . During the coating process, discs were fixed inside the deposition chamber at 15 °C.…”
Section: Methodsmentioning
confidence: 99%
“…During the coating process, discs were fixed inside the deposition chamber at 15 °C. The starting material (synthesis is described elsewhere) was sublimated at 120 °C, which was then pyrolyzed at 540 °C to form into a stream of reactive di‐radical vapor. The stream of reactive di‐radicals then entered the deposition chamber where they deposited and polymerized simultaneously on the discs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffolds were then adsorbed with P1-latex protein using a procedure described by Patel et al to coat PCL substrates. 27 In brief, lyophilized P1-latex protein was prepared in 1 mL Dulbecco's phosphate-buffered saline (DPBS) to obtain 1% (w/v) stock, with a concentration of 0.01 g/mL.…”
Section: P1-latex Protein Adsorptionmentioning
confidence: 99%